Analyzing Mobile Stock Trading Platforms and Their Impact on Individual Investors’ Financial Performance - Vasantha Rao, Taidala; Mahendrababu, Yedukondala; Babu Vemula, Prasanth; Gowri Swetha, Kanuru Sankara; Mahendrababu, Yedukondala (International Journal of Psychosocial Rehabilitation, 2019)
As a fast-growing area in Finance, Information technology (IT) plays an important role in how traders trade online. Investigating whether online trading has a significant effect on financial returns and risks is central to this inquiry. This study, using perceived usefulness and satisfaction categories, addresses how the IT trading platform affects the trader’s trading risk-taking behavior and stock portfolio performance. We examined two unique data sets: 2,726 proprietary online trading accounts and 178 professional investors’ field survey. The results revealed that while the perceived usefulness category presented significant differences between the risk-taking groups and significant impact on stock portfolio performance, the satisfaction category showed no significant results.